Factors of mothers' hesitation in discussing reproductive health - Ratih Indraswari; Zahroh Shaluhiyah; Bagoes Widjanarko; Antono Suryoputro (Intelektual Pustaka Media Utama, 2021)
Reproductive health is always becoming an issue for adolescence. Lack of knowledge, permissive attitude, easy access to pornography and low parental supervision reported as a determinant of risky sexual behavior in adolescence. This study aimed to investigate mother’s perspectives in discussing reproductive health issues with their children aged 9-11 years old. The respondents were 8.046 mothers who had children aged 9-11 years old in Semarang, taken with a purposive sampling technique. Most mother (84.4%) were in adulthood, graduated from Senior High School (50.8%), unemployment (44%), and 47.2% was in low-middle income family. As much as 26.8% of mothers agreed that it is not necessary to inform their children about reproductive health. Talking about reproductive health is taboo for 41.9% of mothers and 38.5% felt awkward. Most of them (71.7%) encountered difficulties in starting reproductive health discussions with their children and 76.1% used other terms to name the genitals to feel more polite. A mother who perceived that delivering reproductive health information is unnecessary (OR 1.44), taboo (OR 1.82), awkward (OR 1.93), and giving courtship permission (OR 1.28) to their children significantly becoming risk factors in practicing reproductive health education. Health workers should help the mothers improve their communication skills, especially in discussing reproductive health with children aged 9-11 years old.